PENDEKATAN KONSELING LINTAS AGAMA DAN BUDAYA DALAM MENCEGAH KEKERASAN DALAM RUMAH TANGGA PADA PASANGAN KERJE MUDE [CROSS CULTURAL AND RELIGIOUS COUNSELING APPROACH IN PREVENTING DOMESTIC VIOLENCE IN KERJE MUDE PARTNERS] - Sutya Dewi; Rois Nafi'ul Umam (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2022)
Kerje mude or early marriage has become a common phenomenon in society, especially the Gayo people who still adhere to local values and traditions. Adolescents who do early marriage or kerje mude in Gayo culture are vulnerable to new situations with various dynamics of psychological problems due to their lack of ability to maintain their emotional stability and lack of maturity and responsibility in living a household life. This can trigger domestic violence and lead to divorce. To prevent this problem from occurring, a cross-religious and cultural counseling approach can facilitate young working couples who have different cultures to be able to know each other's characteristics and culture so that a harmonious family can be built and away from the potential for domestic violence. This research uses a qualitative method with a literature study approach to determine the role of cross-religious and cultural counseling approaches in preventing domestic violence in young working couples. Data collection was carried out by reading and analyzing books and journals on the concept of interfaith and cultural counseling, domestic violence prevention, and work behavior in Nanggroe Aceh Darussalam Province. Data analysis in this study was carried out by reducing data, presenting data, and drawing conclusions. The results showed that cross-religious and cultural counseling is an approach or method that can accommodate differences in background and culture in young working couples in order to build a harmonious household relationship between the two as well as to prevent domestic violence. Counseling across religions and cultures is facilitated by counselors and is carried out in several stages to ensure that the couple is able to live their marriage well.